PENGARUH PENDEKATAN EKSPLORATIF TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN MOTIVASI BELAJAR SISWA - Aisyah, Nurul; Maulana, Maulana; Kurnia, Dadang (Jurnal Pena Ilmiah, 2019)
Mathematical understanding ability is directly proportional with learning motivation. If students can understand the topics, it is possible that students have good learning motivation. Explorative approach can be used as a learning tool that can improve mathematical understanding ability and learning motivation. Explorative approach training the students to explore their knowledge in depth through five stages of learning. This research have purpose to determine the effect of explorative approach and conventional approach on mathematical understanding ability and learning motivation and to determine the relation between mathematical understanding ability and learning motivation. The quasi-experimental method was used in this research with nonequivalent control group design. The sample is the VA class and VB class in SDN 1 Jadimulya. The conclusion obtained is positive influence after using the explorative approach and conventional approach that appear from the improvement of indicators of mathematical understanding abilities and learning motivation and there is a positive correlation between mathematical understanding ability and learning motivation in the medium category.